A fluidez territorial na fronteira ocidental da Amazônia: as cidades gêmeas Tabatinga (Brasil) e Leticia (Colômbia) - Emerson Flávio Euzébio (Confins)
The borders have been studied through different approaches, for instance a recent analysis of the territorial fluidity, considering the intensification of the trans-border flows as a consequence of the current globalizing environment. The goal of the research is to understand the territorial dynamics of the subspace of the twin cities of Tabatinga (Brazil) and Leticia (Colombia) through the analysis of the of infrastructures enabling the trans-border flows and their reflections in the economical and social development of the region. The evaluation of the of fixed infrastructures and the flows system established at local and extra-scale scale allowed the check territorial fluidity and its contribution to the regional development and bringing together of the neighbor communities.